Simulation of solidification process for billet with ϕ350mm section, continuous casted. Issue 1 (January 2016) - Ardelean, E; Lăscuţoni, A; Ardelean, M; Socalici, A; Hepuţ, T
Abstract: The quality of continuous casting product depends both on the quality of the steel, and on technological parameters adopted during the casting and how solidification of billets is conducted. A simulation of the solidifying process is very useful in the industrial casting practice, providing specialists with information about the phenomena during the process and the manner in which certain parameters may vary in order to obtain the desired effects. This paper presents a two-dimensional simulation model that can be used in the continuous casting process, when micro-coolers are used in order to control thermal regime during solidification.